Analysis of CEISA Services User Satisfaction Using the EUCS Method in The Directorate General of Customs and Excise - Awaludin, Muryan; Yolanda, Natasya Erent (SENATIK STT Adisutjipto, 2018)
The purpose of this study is to analyze the factors that influence the satisfaction of users of CEISA services (Customs & Excise Information System and Automation) at the Directorate General of Customs and Excise (DGCE). CEISA uses Single Sign-On (SSO) technology, meaning that users only do one login to be able to access all applications in accordance with their authority. Therefore, the CEISA database and server are centrally managed so that they can be accessed throughout the DGCE office. But in practice there are still DGCE offices that develop independent applications. User satisfaction is one of the important factors that influence the success of implementing an information system. This study uses the End-User Computing Satisfaction (EUCS) method as an indicator of research. The variables tested in this study were 100 respondents as samples taken from employees at the Tanjung Priok Type A Customs and Excise Service Office (CESO). Data analysis using Multiple Linear Regression Test with IBM SPSS Statistics 25 as a tool to process data. There are five hypotheses proposed in this study. The results showed that all proposed hypotheses were accepted. That is, all variables in the EUCS method have a positive and significant effect on CEISA service user satisfaction in the DGCE environment.